Bactericidal Effect of Antibiotics against Bacteria Causing Urinary Tract Infection among Children - Fatima Iqbal, Fariha Nasreen, Sidra Iqbal, Irum Naz, Attiya Elahi, Faisal Rehman (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Urinary Tract Infection (UTI) is one of the most common infections in children. Use of antibiotics according to updated sensitivity pattern is critical. Aim: To determine major bacteria causing UTI with drug sensitivity pattern to find best empirical therapy. Study design: Descriptive cross-sectional study. Methodology: This study was conducted at WAPDA hospital Rawalpindi from June 2022 to November 2022. A total of 71 urine culture positive children aged between 1 to 14 years were enrolled. The main variables for the study included age and sex of patient, isolated bacteria and the sensitivity pattern against different drugs. The data was analyzed using SPSS version 23.0. The variables are presented in the form of standard deviation and frequency of percentages. Results: The average age of enrolled children was 5.9 (SD ± 3.6) years. The common bacteria leading to UTI were E. coli 43 (60.6%) followed by Klebsiella 11 (15.5%) and Enterococcus 5 (7%). The most common organism isolated was E. coli. The most effective drugs against E. coli are Meropenem (97.2%), Fosfomycin (90.2%), and Amikacin (89.7%). The resistance pattern is Co-trimoxazole (86%), Amoxicillin/clavulanic acid (69.8%) and Cefixime (70.7%). Conclusion: The most common isolate was E. coli. The sensitivity of nitrofurantoin, Fosfomycin and Amikacin to the pathogens’ causing UTI is high and can be used empirically. Other commonly used antibiotics are mostly resistant, therefore regular studies in every region are necessary to update the protocols for treatment of UTI. Keywords: Urinary tract infection, E. coli, Amikacin, Urine culture and sensitivity